Usulan Strategi Pemanfaatan Brand Ambassador Untuk Meningkatkan Brand Awareness Rabbani - Nadhirah Fahrani; Cecep Safaatul Barkah; Tetty Herawati; Lina Aulina (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
This study aims to look at the condition of the company's business environment by using SWOT analysis to formulate the right strategy to increase Rabbani's brand awareness. Qualitative research with the case study method is the type of research used. From the analysis results, it is known that the company is in quadrant one, which indicates that it needs a growth strategy. One way to be done is to increase brand awareness through brand ambassadors. Brand ambassadors aim to increase brand awareness and drive sales. The selection of brand ambassadors can be determined by considering the characteristics of brand ambassadors, namely transference, congruence, credibility, attractiveness, and strength.